Vegan versus meat-based pet foods: Owner-reported palatability behaviours and implications for canine and feline welfare. - Andrew Knight (Public Library of Science (PLoS), 2021)
Consumer suspicion of conventional pet foods, along with perceived health benefits of alternative diets, are fuelling development of the latter. These include raw meat diets, in vitro meat products, and diets based on novel protein sources such as terrestrial and marine plants, insects, yeast and fungi. However, some claim vegan diets may be less palatable, or may compromise animal welfare. We surveyed 4,060 dog or cat guardians to determine the importance to them of pet food palatability, and the degree to which their animals displayed specific behavioural indicators of palatability at meal times. Guardians were asked to choose one dog or cat that had been within their household for at least one year, and not on a prescription or therapeutic diet. Of 3,976 respondents who played some role in pet diet decision-making, palatability was the third most important among 12 factors cited as important when choosing pet diets. For 1,585 respondents feeding conventional or raw meat diets, who stated they would realistically consider alternative diets, palatability was the fourth most important among 14 desired attributes. For the 2,308 dogs included, reported observations of 10 behavioural indicators of palatability at meal times reliably indicated significant effects of increased reports of appetitive behaviour by dogs on a raw meat diet, as opposed to a conventional diet. There was no consistent evidence of a difference between vegan diets and either the conventional or raw meat diets. For the 1,135 cats included, reported observations of 15 behavioural indicators indicated that diet made little difference to food-oriented behaviour. Based on these owner-reported behaviours, our results indicate that vegan pet foods are generally at least as palatable to dogs and cats as conventional meat or raw meat diets, and do not compromise their welfare, when other welfare determinants, such as nutritional requirements, are adequately provided.